Photosynthetic Activity Measured In Situ in Microalgae Cultures Grown in Pilot-Scale Raceway Ponds - Masojídek, Jiří; Štěrbová, Karolína; Robles Carnero, Victor A; Torzillo, Giuseppe; Gómez-Serrano, Cintia; Cicchi, Bernardo; Câmara Manoel, João Artur; Silva Benavides, Ana Margarita; Barceló-Villalobos, Marta; Pozo Dengra, Joaquín; Ördög, Vince; Gómez Pinchetti, Juan Luis; et al. (Plants (Basel, Switzerland), 2024)
The microalga Scenedesmus sp. (Chlorophyceae) was cultured in a raceway pond (RWP) placed in a greenhouse. The objective of this case study was to monitor the photosynthesis performance and selected physicochemical variables (irradiance, temperature, dissolved oxygen concentration) of microalgae cultures in situ at various depths of RWP. The data of actual photochemical yield Y(II), the electron transport rate monitored by in vivo chlorophyll fluorescence and photosynthetic oxygen production both in situ and ex situ revealed that (i) even in diluted cultures (0.6 g DW L-1), the active photic layer in the culture was only about 1 cm, indicating that most of the culture was "photosynthetically" inactive; (ii) the mechanism of non-photochemical quenching may not be fast enough to respond once the cells move from the surface to the deeper layers; and (iii) even when cells were exposed to a high dissolved oxygen concentration of about 200% sat and higher, the cultures retained a relatively high Y(II) > 0.35 when monitored in situ. The presented work can be used as exemplary data to optimize the growth regime of microalgae cultures in large-scale RWPs by understanding the interplay between photosynthetic activity, culture depth and cell concentration.
Keywords: RWP; oxygen production; photosynthesis; photic layer; electron transport; green microalgae; chlorophyll (Chl) fluorescence; Scenedesmus; non-photochemical dissipation